Penguatan Kesadaran Kesehatan Pasien melalui Strategi Promosi Kesehatan Rumah Sakit sesuai Permenkes No. 44/2018 - Meithia, Artha; Adyas, Atikah; Nugroho, Yudhinanto Cahyo; Noviansyah, N (Universitas Muhammadiyah Pekajangan Pekalongan, 2024)
This study aims to provide insight into the relationship between the health promotion strategies implemented by Azizah Hospital and the increase in public health awareness, particularly among inpatients. The research uses a quantitative approach with a cross-sectional design. This approach analyzes the relationship between health promotion strategies in the areas of advocacy, partnership, community empowerment, and conducive environment on the increase in health awareness among inpatients at Azizah Hospital. Additionally, the study involves the use of literature from books, journals, and articles focusing on the quality of services in inpatient wards. The results from 270 inpatient respondents at Azizah Hospital show that the average age of patients is 35 years, with 62.6% being female. This indicates that most inpatients are adults to elderly individuals. The multivariate test using multiple linear regression shows that the beta coefficient for the health promotion strategy in the partnership domain is 0.176, in the community empowerment domain is 0.328, and in the conducive environment domain is 0.346. In conclusion, the variable that has the most significant impact on increasing health awareness among inpatients is the conducive environment variable.